Expanded Criteria Donors in Kidney Transplantation: The Role of Older Donors in a Setting of Older Recipients. (4th June 2013) - De Rosa, Paride; Muscogiuri, Giovanna; Sarno, Gerardo
Abstract : Kidney transplantation (KT) is the therapy of choice for end-stage renal disease (ESRD). The ESRD population is aging and so are patients waiting for KT. New strategies have been made for increasing the donor and recipient pools, and as a consequence kidneys from older donors or donors with significant comorbidities, the so-called "expanded criteria donor" (ECD) kidneys, are used for transplantation. Although good outcomes have been achieved from ECD, several issues are still waiting for clarification and need to be discussed. The concept of age matching is accepted as a method to ameliorate utilization of these allografts, but an optimal and widely accepted strategy is still not defined. The development of machine perfusion and the dual kidney transplantation are techniques which further improve the outcome of transplants from ECD, but the described experiences are scarce or coming from small single institutional reports. Also due to age-related immune dysfunction and associated comorbidities, the elderly recipients are more susceptible to immunosuppression related complications (e.g., infections and malignancy), although a widely accepted and validated immunosuppressive regimen is still lacking. In this paper, we review the issues related to KT employing allografts from marginal donors with a particular interest for the elderly patients.